Research of recipe components influence on the properties of dairy-protein mashes for semi-finished products - Grek, Olena; Tymchuk, Alla; Tsygankov, Sergii; Onopriichuk, Olena; Savchenko, Oleksandr; Ochkolyas, Оlena (Eastern-European Journal of Enterprise Technologies, 2019)
The paper reports a study into the influence of formulation components, such as potato fiber, white sugar and egg mélange, on the characteristics of milk-protein mashes for heat-treated semi-finished products. We studied the effective viscosity and moisture-retaining power of mashes and found out a significant influence of potato fiber in the amount from 0.5 % to 2.0 % on characteristics. A tendency has been observed to a decrease in the above-indicated values with the addition of 10 % of white sugar in all model samples. It was found that egg mélange also reduced the moisture-retaining power of mashes by 13.5±0.6 % and effective viscosity by 76.0±1.4 Pa·s on average, but there was the opposite effect at heat treatment of semi-finished products. Taking into account the overall influence of all components, it is rational to add 1.5 % of "Potex" and 10 % of sugar and 10 % of egg mélange to the cottage cheese (instead of wheat flour). According to the indicators of water activity (аw) in milk-protein mashes, we found that the addition of potato fiber in the above amounts reduced the specified indicator from 0.961 to 0.952. аw was at the level of 0.964 in the control mash with wheat flour. Binding of water occurred at the activation of aqueous systems of milk-protein mashes and spoilage processes slowed down. The influence of various heat treatment (frying at temperature of (155±5 °С) and baking (185±5 °С) on qualimetric indicators of semi-finished products has been established. We observed the smallest weight losses in the sample with 2.0 % of potato fiber. They were 4.3±0.2 % and 6.2±0.1 %, respectively. The study results confirmed the possibility of using the specified above component to reduce the weight losses of semi-finished products after heat treatment. The addition of "Potex" provided necessary efficiency in the processing of milk-protein mashes for mechanical shaping of semi-finished products